The Effect of Auditor Competence, Independence, and Integrity on Audit Quality: A Case Study on BPKP Auditors - Insanuadi, Mohammad; Muhyarsyah, Muhyarsyah (Kontigensi : Jurnal Ilmiah Manajemen, 2025)
Auditor competence plays a crucial role in ensuring technical proficiency, accurate analysis, appropriate decision-making, and maintaining the credibility and quality of an objective and reliable audit. This study aims to analyze the effect of auditor competence, auditor independence, and auditor integrity on audit quality. A quantitative approach using multiple linear regression analysis was employed to analyze the research data. The research findings reveal that the three independent variables: auditor competence, independence, and integrity have a positive and significant effect on audit quality. These findings reaffirm that auditor competence, independence, and integrity are crucial factors in enhancing audit quality. Additionally, this study contributes to policy development aimed at improving audit quality, particularly in the public sector, by emphasizing the strengthening of the auditor’s role in ensuring high-quality audit outcomes.